Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/yea.320070804
|View full text |Cite
|
Sign up to set email alerts
|

Four major transcriptional responses in the methionine/threonine biosynthetic pathway of Saccharomyces cerevisiae

Abstract: Genes encoding enzymes in the threonine/methionine biosynthetic pathway were cloned and used to investigate their transcriptional response to signals known to affect gene expression on the basis of enzyme specific-activities. Four major responses were evident: strong repression by methionine of MET3, MET5 and MET14, as previously described for MET3, MET2 and MET25; weak repression by methionine of MET6; weak stimulation by methionine but no response to threonine was seen for THR1, HOM2 and HOM3; no response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
83
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 73 publications
3
83
0
Order By: Relevance
“…3b, nt -172 to -162). Mountain et al (32) found that the mRNA of MET5, another gene believed to be necessary for formation of YSiR, is under general amino acid control. However, no sequence data are available for this gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3b, nt -172 to -162). Mountain et al (32) found that the mRNA of MET5, another gene believed to be necessary for formation of YSiR, is under general amino acid control. However, no sequence data are available for this gene.…”
Section: Resultsmentioning
confidence: 99%
“…This is not possible for YSiR, which seems to lose all prosthetic groups and associated enzymatic activities if treated with denaturing agents (25). All of the S. cerevisiae mutations unambiguously assigned to the step of sulfite reduction, i.e., meti, metS, met8, met1O, and met2O (30,31,52), have been located to different chromosomes, but so far only genes complementing metS and met8 have been cloned (11,32). The MET5 mRNA has a size of 5.5 kb (32), which suggests that it might encode the 167-kDa subunit of YSiR (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of this research is to define the genetic factors leading to sulfide formation so that genetic strategies can then be used to identify or create commercial strains that will not produce hydrogen sulfide under winemaking conditions. Control of the sulfate reduction pathway is multifaceted and responsive to numerous regulatory inputs (6,8,14,26,29,30). As a consequence, mutational change of a wide array of genes may impact sulfide formation and release.…”
mentioning
confidence: 99%
“…As a consequence, mutational change of a wide array of genes may impact sulfide formation and release. Sulfite reductase is responsible for reducing sulfite to sulfide and is regulated by general amino acid control, as well as methionine (26). Other research suggests that cysteine or its derivatives, rather than methionine, is the main end product regulating pathway activity (14,29).…”
mentioning
confidence: 99%